2022
DOI: 10.1111/bph.15951
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor activation impairs antitumour activity of natural killer cells

Abstract: Background and purpose: A high number of intratumoural infiltrating natural killer (NK) cells is associated with better survival in several types of cancer, constituting an important first line of defence against tumours. Hypoxia in the core of solid tumours induces cellular stress and ATP release into the extracellular space where it triggers purinergic receptor activation on tumour-associated immune cells. The aim of this study was to assess whether activation of the purinergic receptor P2X7 by extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Consistent with this and as discussed above, this mAb also altered the proportions of hTregs, hNK T cells, and hTh17 cells, and so collectively, a greater number of lymphocyte subsets are impacted by the anti-hP2X7 mAb than by any of the small molecule P2X7 antagonists used previously in this model [ 20 , 21 , 22 , 37 ]. Of note, it has been observed that P2X7 activation impairs the antitumour activity of NK cells to human chronic myeloid leukaemia K562 cells [ 54 ]. Thus, combined with the notion that NK cells may help to both prevent GVHD and contribute to graft-versus-leukaemia immunity [ 55 ], use of an anti-hP2X7 mAb in such recipients may help improve outcomes in people with leukaemia following allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this and as discussed above, this mAb also altered the proportions of hTregs, hNK T cells, and hTh17 cells, and so collectively, a greater number of lymphocyte subsets are impacted by the anti-hP2X7 mAb than by any of the small molecule P2X7 antagonists used previously in this model [ 20 , 21 , 22 , 37 ]. Of note, it has been observed that P2X7 activation impairs the antitumour activity of NK cells to human chronic myeloid leukaemia K562 cells [ 54 ]. Thus, combined with the notion that NK cells may help to both prevent GVHD and contribute to graft-versus-leukaemia immunity [ 55 ], use of an anti-hP2X7 mAb in such recipients may help improve outcomes in people with leukaemia following allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…This 7.5-Mb region shows an extended reduction in nucleotide diversity relative to other clades (Additional file 2: Fig. S5), and includes genes associated with canine body size and height [4] as well as glioma risk [123] and other cancer phenotypes [124][125][126].…”
Section: Discussionmentioning
confidence: 99%